Effect of Irrigation and Fertilizer on the Yield and Quality of Seed Cotton (Gossypium hirsutum L.) in Western Rajasthan - Singh, Attar (Annals of Arid Zone, 2016)
Results of two years data indicated that branching, flowering and seed development were the most critical stages of irrigation in cotton and gave 566 kg/ha seed cotton yield during 1974 and a mean yield of 350 kg/ha. It remained at par with higher number of irrigations. Soil being moderate in fertility. the control treatment gave 331 kg/ha yield of seed cotton and higher levels of fertility did not push up the yields. When the irrigations were applied at branching, flow ring and seed formation stages of plant growth, best quality of cotton fibre was obtained as judged by different indices namely short fibre percentage, maturity of fibre and fibre fineness which were all desirable in this case.